Calsyntenin-1 Negatively Regulates ICAM5 Accumulation in Postsynaptic Membrane and Influences Dendritic Spine Maturation in a Mouse Model of Fragile X Syndrome - Cheng, Ke; Chen, Yu-shan; Yue, Chao-xiong; Zhang, Si-ming; Pei, Ya-Ping; Cheng, Gui-rong; Liu, Dan; Xu, Lang; Dong, Hong-xin; Zeng, Yan (Frontiers in Neuroscience, 2019)
Fragile X syndrome (FXS) is a neurodevelopmental disorder that causes intellectual disability, as well as the leading monogenic cause of autism spectrum disorders (ASD), in which neurons show aberrant dendritic spine structure. The reduction/absence of the functional FMRP protein, coded by the X-linked Fmr1 gene in humans, is responsible for the syndrome. Targets of FMRP, CLSTN1 and ICAM5, play critical roles in the maturation of dendritic spines, synapse formation and synaptic plasticity. However, the implication of CLSTN1and ICAM5 in dendritic spine abnormalities and the underlying neuropathologic processes in FXS remain uninvestigated. In this study, we demonstrated that CLSTN1 co-localizes and co-transports with ICAM5 in cultured cortical neurons. Also we showed that shRNA-mediated downregulation of CLSTN1in cultured WT neurons increases ICAM5 on the surface of synaptic membrane, subsequently affecting the maturation of dendritic spines. Whereas, normalization of CLSTN1 level in Fmr1 KO neurons reduces ICAM5 abundance and rescues impaired dendritic spine phenotypes. Most importantly, CLSTN1 protein is reduced in the postnatal medial prefrontal cortex of Fmr1 KO mice, which is correlated with increased ICAM5 levels on the surface of synapses and excessive filopodia-like spines. In conclusion, this study demonstrates that CLSTN1 plays a critical role in dendritic spine formation and maturation in FXS by regulating ICAM5 redistribution.